GREELA: green pulsed electric field-asissted extraction of Spirulinna sp. Carotenoid for enriched-olive oil to achieve sustainable high vitamin a oil availability / Annisa Aurora Kartika and Ulfatu Mahmuda - Kartika, Annisa Aurora; Mahmuda, Ulfatu (Universiti Teknologi MARA, Kedah, 2019)
Vitamin A deficiency (KVA) is one of the nutritional problems in Indonesia which is often referred to as the problem of micronutrient or hidden hunger. One effort to overcome KVA is through daily non-food intake, such as supplements rich in carotenoids. Carotenoids as pro-vitamin A, are widely used in various sectors as nutraceutical, cosmetical, and supplements. According to WHO (2015), high carotenoid supplementation can be an alternative step to overcome KVA. On the other hand, one of the plants containing high carotenoids is Spirulina sp., with several advantages including low cost of cultivation, fast growth, has a high enough protein content, and is easier to extract. In its cultivation, Malang Raya is one of the right locations for developing Spirulina sp micro algae. Where Malang Raya has a good supply of marine and freshwater waters. GREELA, comes as a solution to these two main problems. GREELA is a breakthrough innovation supplement that combines the advantages of Spirulina sp. Microalgae, produced with Electric Pulse technology Field-assisted as an extraction method and olive oil as a carotenoid solvent, with high carotenoids produced with environmentally friendly technology in order to create a good environment for human life in the present and future. In addition, the use of GREELA is more time-efficient and efficient. Where the use of making caroteoid extract takes 24 hours, now it only takes 60 seconds. GREELA has total carotenoids of 1802.25 μg / gr with high activity. Moreover, there is no solvent residue in the manufacturing process so that it is classified as environmentally friendly technology that is feasible to develop and commercialization.